Comparative Study on Routing Protocol in Mobile Ad Hoc Networks using Soft Computing Techniques - Singh, Amarjit; Singh, Tripatdeep (International Journal of Computer Sciences and Engineering, 2019)
Mobile Ad Hoc Network is able to communicate with different nodes. In this research paper we are mainly in view of the study of routing protocols in mobile ad hoc networks. As we know, still there are numbers of diverse metrics to work on. In the MANET, we are study basically a few numbers of metrics such as delay and energy-throughput in mobile ad hoc networks. According to this, further concise the study related these metrics. This research paper includes relative with different techniques and future work is also applicable.